Economic Valuation of Social Forestry Areas in Soppeng Regency, South Sulawesi Province, Indonesia - Inri Agreis Pasomba; Irma Sribianti; Mohammad Natsir; Ratnawati Tahir; Sri Mardiyati (International Journal of Business and Quality Research, 2025)
This study aims to analyze the types of forest products and the economic valuation value of forests in social forestry in Mattabulu Village, Soppeng Regency, South Sulawesi Province, Indonesia. The sampling technique used was purposive sampling, namely selecting farmers who are members of the Social Forestry Business Group (KUPS), so that 85 respondents were obtained from 5 KUPS. The types of data are primary and secondary data. The data analysis technique uses quantitative and qualitative descriptive. The results of this study indicate that the types of forest products in social forestry in Mattabulu Village include non-timber forest products consisting of: coffee, sugar palm, candlenut, ginger, and honey commodities. The annual economic valuation value of non-timber forest products in Mattabulu Village includes: coffee of IDR 385,335,000.00, sugar palm of IDR 945,830,000.00, candlenut of IDR 109,853,000.00, ginger of IDR 425,390,000.00, and honey of IDR 41,713,000.00. The annual economic valuation value of forest environmental services management and utilization includes: biodiversity reaching IDR 7,634,692,000.00, water utilization of IDR 30,311,000.00 and carbon absorption of IDR 10,944,067,680.00. The total economic value of non-timber forest products and forest environmental services in Mattabulu Village can reach IDR 20,517,168,680.00 per year.